PENGARUH DEFISIT ANGGARAN, KURS RUPIAH DAN CADANGAN DEVISA TERHADAP PERTUMBUHAN EKONOMI INDONESIA SELAMA TAHUN 2014-2023 - MURBAYANI, MURBAYANI (Patria Artha University, 2024)
This research aims to analyze the influence of the Budget Deficit, Rupiah Exchange Rate, and Foreign Exchange Reserves on Indonesia's economic growth (GDP). The type of data used is the time series from 2014-2023. Secondary data is in the form of Budget Deficit (Rupiah), GDP based on constant 2010 prices, Rupiah exchange rate (against the US Dollar) and Foreign Exchange Reserves (Billions of Rupiah). The analytical method used in this research is multiple linear regression analysis. Based on the results of the research analysis, it can be concluded that the Budget Deficit has a negative but not significant effect on Indonesia's Economic Growth during the 2014-2023 period. The Rupiah Exchange Rate (Kurs) has a positive and significant effect on Indonesia's Economic Growth during the 2014-2023 period. This shows that the increase in the US Dollar exchange rate resulted in an increase in Indonesia's Economic Growth. Foreign Exchange Reserves have a positive and significant effect on Indonesia's Economic Growth during the 2014-2023 period. This shows that the increase in foreign exchange reserves resulted in an increase in Indonesia's economic growth (GDP) during the 2014-2023 period.